Penerapan Model Pembelajaran Snowball Throwing Sebagai Strategi Untuk Meningkatkan Motivasi Belajar Siswa Dalam Pendidikan Pancasila: Penerapan Model Pembelajaran Snowball Throwing Sebagai Strategi Untuk Meningkatkan Motivasi Belajar Siswa Dalam Pendidikan Pancasila - Pradnyawati, I Gusti Ayu Widya; Suastika, I Nengah; Dewi Adhi Utami, Anak Agung Istri; Febriana Putra Wijaya, I Putu Agus; Santya Isana Pertiwi, Ni Ketut; Dinda Juliastri, Ni Luh; Kanya Diva Gayatri, Komang Ayu; Erliana Dewi, Ketut (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2025)
This study aims to describe the application of the Snowball Throwing learning model as a strategy to increase students' learning motivation in Pancasila Education subjects. The background of this research is the low motivation of students to learn, which can be seen through observations in class VII B of SMP Negeri 1 Seririt. Snowball Throwing is a cooperative learning model that emphasizes interaction between students in composing and throwing questions in an active and fun learning atmosphere. This study uses a descriptive qualitative approach with implementation case study design, as well as data collection techniques through observation, in-depth interviews, and field notes. The results of the study show that the application of this model is able to increase students' motivation to learn which is shown through increased activeness, courage to ask and answer, and involvement in group discussions. The change in motivation that occurs is profound, showing the transition from extrinsic motivation to intrinsic motivation. This method succeeded in creating a psychologically safe learning environment and changed students' perceptions from viewing learning as a boring (teacher-centered) activity to an interactive and dynamic activity. Thus, Snowball Throwing is considered effective to be applied as an innovative strategy in increasing student learning motivation, especially in learning Pancasila Education.